Спектры ПМР основных молибдатов РЗЭ - Перепелица, Александр Петрович; Калиниченко, А. М. (My University, 1977)
Из водных растворов получены основные молибдаты R(OH)MoO4, R- La-Lu, Y, Sc. Соединения исследованы методом ПМР-спектроскопии, установлена зависимость ширины линии ПМР от порядкового номера РЗЭ. Basic molybdates R(OH)MoO4, R-La-Lu, Y, Sc., are preparated into water solution. Compounds are inverstigated by method PMR-spectroscopy, the dependence of width line of spectrum PMR from ordinal number r.e.e. is determinate.
Keywords: изменение; основные молибдаты; лантан-лютеций; скандий; иттрий; спектры ПМР; spectrums of PMR; change; basic molybdates; lantanum-lutecium; itrium; scandium; кафедра харчової хімії